Requirements for effective professional IT-training: a case study - Reiners, Torsten; Fuchs, V. (EdITLib, 2011)
In companies, it is common practice to provide continuous training and skill enhancement. Unfortunately, this is often done without comprehensive pre-evaluations of requirements for coming tasks and suitability for the participant. Moreover, companies attempt to reduce overall costs by booking training units for larger groups; independent of needs, preknowledge, or working area of the participants. Thus, continuing training is covered but often it is more time-off-duty than effective time for sustainable training. In this paper, we analyzed almost thousand participants in an empirical study to understand the interdependencies of their background, course selection, tutor, course material, mode of learning; i.e. with respect to effectiveness and sustainability. The outcome shows the importance of pre-determining the requirements compared to other factors.